Operação urbana consorciada Água Espraiada: Um olhar sobre a distribuição da chuva na fonte - Callegaro, Claudete Gebara José (2014)
There are many centuries that the rain, in the city, is not understood as life ; it incorporates road and health infrastructure, confined to gutters, manholes, underground galleries, returning to people perception like floods. Nowadays, the understanding about eco-systemic relationships brings new models for managing urban storm water, in the way of bioclimatic architecture, designing with nature, with contemporary principles of environmental comfort in the cities, i. e., sustainable urban development. The speech is ready; how to transfer theory into practice is one of the objectives of this work. Some places in the world have adopted this paradigm and developed methodology for public and private actions, according to a model called the green infrastructure system. Professionals in individual works also believe in that path, contributing with creative design, showing the model potential. By this principle, every place has its unique design, according to its physical territory and the cultural characteristics of its society. Considering that joint urban operations are the most advanced in urban policy for development, in Brazil, do they incorporate the urban sustainability principles brought by the green infrastructure model? That is what will be analyzed, in reference to the Água Espraiada Joint Urban Operation, in São Paulo.